2014
DOI: 10.1186/1471-2458-14-355
|View full text |Cite
|
Sign up to set email alerts
|

A survey of retirement intentions of baby boomers: an overview of health, social and economic determinants

Abstract: BackgroundGovernments have been implementing policies aimed at halting the trend towards early retirement for Baby Boomers. Public policies can have a strong effect on when a person retires and this analysis contributes to an improved understanding of retirement aspirations in regards to health, social, workplace and economic determinants.MethodsIn October 2011 a telephone survey was undertaken with participants aged 50 to 65 years who were in paid employment and who had been in the workforce for the previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…Evidence in Australia shows that transition to retirement can occur over a broad age‐span extending from the ages of 40 to 70 years (Sander & Bell, ). In the coming years, the median age of retirement will rise with changes to the pension eligibility age in many countries, such as England and Australia (Taylor, Pilkington, Feist, Dal Grande, & Hugo, ). This is likely to result in a delayed peak in mobility, with people moving later in preparation for retirement.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence in Australia shows that transition to retirement can occur over a broad age‐span extending from the ages of 40 to 70 years (Sander & Bell, ). In the coming years, the median age of retirement will rise with changes to the pension eligibility age in many countries, such as England and Australia (Taylor, Pilkington, Feist, Dal Grande, & Hugo, ). This is likely to result in a delayed peak in mobility, with people moving later in preparation for retirement.…”
Section: Resultsmentioning
confidence: 99%
“…However, disability pensions only account for a minority of all pensions; a greater impact on the public economy may Virtanen et al come from the remaining working population having the potential to prolong their work careers voluntarily. Some studies have examined intentions (rather than actual decisions) of people to continue working after the age of 65 years and found that high education (a correlate of high occupational class), good physical health, and good psychosocial working conditions were associated with intentions to work longer (15)(16)(17). Some studies have focused on "bridge employment", that is, having a paid job after retirement.…”
mentioning
confidence: 99%
“…There were three qualitative studies (Pillay et al . ; Quine, Bernard & Kendig, ; Shacklock, ), 11 quantitative studies (de Vaus, Wells, Kendig & Quine, ; Jackson & Walter, ; Kendig et al ., ; Knox; McPhedran, ; Noone, O'Loughlin & Kendig, ; Pillay, Kelly & Tones, , ; Schofield & Beard, ; Schofield, Fletcher, Page & Callander, ; Taylor, Pilkington, Feist, Dal Grande & Hugo, ) and one paper containing both quantitative and qualitative studies (Quine, Wells, de Vaus & Kendig, ). Using the National Health and Medical Research Council () levels of evidence, there were two Level III‐2 studies, one Level III‐3 study and 13 Level IV studies (Table ).…”
Section: Resultsmentioning
confidence: 99%